Adaptive back‐stepping sliding mode attitude control of missile systems. (3rd January 2013) - Xia, Yuanqing; Lu, Kunfeng; Zhu, Zheng; Fu, Mengyin; Li, Shihua; Frye, Michael T.; Qian, Chunjiang
SUMMARY This paper is devoted to the attitude control of a quaternion missile model, which is nonlinear in aerodynamics with atmospheric moment uncertainties, inertia uncertainties, bounded disturbances and actuator failures. By employing the back‐stepping technique, the corresponding sliding mode controller is designed to guarantee the state variables of the closed loop system to converge to a small region of the reference states with the help of the adaptive law by estimating the total uncertainties, and be chatter‐free. Also, simulation results are presented to illustrate the effectiveness of the control strategy. Copyright © 2013 John Wiley & Sons, Ltd.